Development of an odorant emission model for sewage treatment works - Gostelow, P (Water science and technology : a journal of the International Association on Water Pollution Research, 2001)
In the field of odour assessment, much attention has been paid to the measurement of odour concentration. Whilst the concentration of an odour at a receptor is a useful indicator of annoyance, the concentration at the source tells only half the story. The emission rate - the product of odour concentration and air flow rate - is required to appreciate the significance of odour sources. Knowledge of emission rates allows odour sources to be ranked in terms of significance and facilitates appropriate selection and design of odour control units. The emission rate is also a key input for atmospheric dispersion models. Given the increasing importance of odour to sewage treatment works operators, there is a clear need for predictive methods for odour emission rates. Theory suggests that the emission of odorants from sewage to air is controlled by mass transfer resistances in both the gas and liquid phase. These are in turn controlled by odorant and emission source characteristics. The required odorant characteristics are largely known, and mass transfer from many different types of emission sources have been studied. Sewage treatment processes can be described by one or more of six characteristic emission sources, these being quiescent surfaces, channels, weirs and drop structures, diffused aeration, surface aeration and flow over media. This paper describes the development of odorant mass transfer models for these characteristic emission types. The models have been applied in the form of spreadsheet models to the prediction of H2S emissions and the results compared with commercial VOC emission models